Answer:
x = x - 4/6
false
Step-by-step explanation:
6(x - 1) - 4x = 2(3x - 5)
First, lets distribute the 6 to each item inside the parentheses on the left side. You can do this by multiplying the 6 by each term.
6 * x = 6x
6 * -1 = -6
6x - 6 - 4x = 2(3x - 5)
Next, we will combine like terms.
6x - 4x = 2x
2x - 6 = 2(3x - 5)
Now, let's look at the right side of the equation.
Let's distribute the 2 to each item inside the parentheses on the left side. You can do this by multiplying the 2 by each term.
2 * 3x = 6x
2 * -5 = -10
6x - 1 = 6x - 5
Immediately, we can tell this is false, but let's solve the equation just to make sure.
6x - 1 = 6x - 5
+1 +1
6x = 6x - 4
--- --------
6 6
x = x - 4/6
This is false.
Answer:
2
Step-by-step explanation:
2 is the only common factor between 8 and 14
SA=4pir^2
SA=4pi13^2
SA=4pi169
SA=676pi ft^2
0.04, or 4 hundredths is 10 percent of 0.40
10 times 0.04 gives you 0.40
How much does each bamboo plant cost. This is impossible to solve without knowing the cost. I you have the cost i would be happy to help.